Inovasi Metode Pembelajaran Al-Qur'an untuk Menangkal Dampak Negatif Teknologi pada Anak Sekolah Dasar di Kota Banjarmasin - Muhammad Arifin; Wulandari, Arina; Sa’adah Erliani (putrapublisher.org, 2025)
Innovation of Al-Qur'an learning methods in facing technological developments. The background of the study is the importance of learning the Al-Qur'an from an early age amidst the challenges of digital disruption. This study aims to identify innovative strategies for learning the Al-Qur'an that are relevant, interesting, and consider socio-cultural values. This study uses a qualitative approach with a descriptive research type and survey method. Data were collected through observation, interviews, documentation at SDIT Ukhuwah and SDIT Sabilal Muhtadin Banjarmasin. This data collection technique uses interviews, observation sheets to evaluate learning methods, student involvement, and the influence of technology. Primary data sources are teachers, students. The results of the study that applied the innovative learning methods of Ummi and Tilawati, the Ummi method prioritizes a simple, fun, and heart-touching approach. The results of this study state that the Tilawati method focuses on interactive learning of the classical Simak reading technique. Both methods are designed to help students master reading the Al-Qur'an in tajwid and tartil. Innovation of the Al-Qur'an learning method is able to answer the challenges of the digital era by integrating an approach based on Islamic values ​​and technology. This provides a great opportunity to increase students' interest and understanding of the Qur'an, while strengthening character and morals.